Clinical, Sleep, and Chronobiological Characteristics of Children with Smith–Magenis Syndrome Under Treatment for Sleep Disorders. - Comajuan, Marion; Guyon, Aurore; Raverot, Véronique; Babinet, Marie-Noelle; Lioret, Julien; Brunel, Lisa; Claustrat, Bruno; Demily, Caroline; Franco, Patricia (Children, 2025)
Highlights: What are the main findings? Children with Smith–Magenis syndrome showed persistent short and poor-quality sleep despite treatment. Very high melatonin levels persisted after treatment withdrawal, suggesting possible iatrogenic accumulation in children receiving very high doses, whose melatonin metabolism (potentially involving slow metabolizers) remains poorly understood. What are the implications of the main findings? Routine monitoring of salivary melatonin and personalized dose titration could optimize treatment, avoid overexposure, and improve both sleep and behavior. Non-pharmacological approaches such as controlled light therapy and other chronobiotic strategies may represent promising complementary or alternative options to improve circadian alignment in SMS. Background/Objectives: Smith–Magenis Syndrome (SMS) is a rare neurodevelopmental disorder characterized by severe sleep disturbances and an advanced melatonin rhythm. Current treatments, mainly exogenous melatonin and β-blockers, have not been evaluated in children. This study aimed to characterize the clinical, sleep, and chronobiological profiles of children with SMS under treatment and to assess the effects of melatonin and β-blockers. Methods: In this prospective, single-center study, 20 children with genetically confirmed SMS (aged 5–13 years; 55% female) underwent 15-day home actimetry and 48 h hospitalization, during which questionnaires, polysomnography (PSG), and salivary melatonin/cortisol profiling were performed. Melatonin and psychostimulants were discontinued 36 h before hospitalization. Results: Overall, 95% of children received melatonin and 20% β-blockers. Despite treatment, insomnia was reported in 90%, excessive daytime sleepiness in 65%, and learning problems in 90%. On actimetry, melatonin improved the mean nocturnal awakening duration (1.4 vs. 2.3 min, p = 0.040), wake-up time (06:50 vs. 06:11, p = 0.004), and longest continuous sleep episode (398 vs. 317 min, p = 0.040), but had little effect on the total sleep time, efficiency, and midpoint of sleep. Very high daytime salivary melatonin persisted (median peak 169.50 pg/mL) despite the last exogenous melatonin intake being more than 48 h prior to sampling, suggesting possible iatrogenic accumulation. The median peak in melatonin occurred at 11:57 and that in cortisol at 08:22. In children with β-blockers, there was a tendency toward an earlier melatonin peak but also toward delayed sleep onset, increased nocturnal awakenings, and reduced total sleep. Conclusions: Children with SMS showed persistent sleep difficulties and an advanced circadian phase despite sleep treatments. Exogenous melatonin provides partial benefit but may lead to daytime accumulation, while β-blockers may have adverse sleep effects despite beneficial effects on melatonin peak secretion, warranting further study.